Eccentric triboelectric nanosensor for monitoring mechanical movements. (August 2019) - Qu, Zhigang; Wu, Liqun; Yue, Bin; An, Yang; Liu, Zirui; Zhao, Pengfei; Luo, Jikui; Xie, Yuedong; Liu, Ying; Wang, Qiuyu; Wang, Zhiyuan; Dai, Rui; et al.
Abstract: For mechanical equipment or facilities, abnormal vibration and external impact can sometimes cause fatigue or even failure, which might lead to severe accidents. It's necessary to monitor the movement of important devices during their service and identify these abnormal conditions. In recent years, triboelectric nanogenerators (TENGs) have been widely used for collecting energy in many applications, and many experiments show that it is an effective method for self-powered sensing. In this paper, a mathematical model of a novel self-powered eccentric triboelectric nanosensor (Ec-TENS) has been built which can detect linear acceleration and velocity. Governing equations between output voltage and linear acceleration/velocity have been derived. Based on the theoretical model, a sliding-mode prototype has been designed and fabricated to verify the theoretical models through a series of tests. Experimental results have shown that Ec-TENS could generate output voltage once external acceleration exceeds a threshold, and amplitude of voltage could vary with velocity. The output voltage and linear velocity satisfy a specific function, and have a good repeatability and stability. Because of its self-powered feature, the novel Ec-TENS has potentially wide applications in the fields of structural health monitoring (SHM), wearable devices, security systems and aeronautic fields, especially in extreme environmental or unattended conditions. Graphical abstract: Image 1 Highlights: Proposed a novel design of a self-powered eccentric triboelectric nanosensor. Proposed a theoretical model, governing equations and verified them by tests. It can detect linear velocity and acceleration change without a power supply.